2018
DOI: 10.1016/j.bjm.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Study of pandrug and heavy metal resistance among E. coli from anthropogenically influenced Delhi stretch of river Yamuna

Abstract: Escalating burden of antibiotic resistance that has reached new heights present a grave concern to mankind. As the problem is no longer confined to clinics, we hereby report identification of a pandrug resistant Escherichia coli isolate from heavily polluted Delhi stretch of river Yamuna, India. E. coli MRC11 was found sensitive only to tobramycin against 21 antibiotics tested, with minimum inhibitory concentration values >256 μg/mL for amoxicillin, carbenicillin, aztreonam, ceftazidime and cefotaxime. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Development was statistically better under microaerophilic conditions (p<0.05). These results corroborate those of the previous studies that reported the ability of E. coli to form biofilms on polystyrene under different conditions [35]. However, this result differs from that reported by Auger [26], who had observed that anaerobic conditions slowed the development of biofilms considerably.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Development was statistically better under microaerophilic conditions (p<0.05). These results corroborate those of the previous studies that reported the ability of E. coli to form biofilms on polystyrene under different conditions [35]. However, this result differs from that reported by Auger [26], who had observed that anaerobic conditions slowed the development of biofilms considerably.…”
Section: Discussionsupporting
confidence: 91%
“…Zeraik and Nitschke [44] and Azam et al . [35] showed that supplementation of culture medium with various substances influenced significantly their ability to form biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, heavy metal resistance genes for mercury ( merACDTPR ), arsenic ( arsRBC ), nickel ( nikABCDE ), copper ( pcoABCDR , cusABCFRS , cueOR , cutA ), zinc ( znuABC , zntAR , zitB , zraR ), and silver ( silABCEFPS ) were identified in E. coli B2C strain. The presence of several heavy metal resistance genes in E. coli strain B2C seems unusual compared to other E. coli strains recovered from the environment ( Azam et al, 2018 ; Siddiqui et al, 2020 ). However, this difference could be due to the use of whole-genome sequencing, whereas most studies describe the detection of a few selected genes using PCR alone.…”
Section: Resultsmentioning
confidence: 83%
“…In this regard, heavy metals seem to facilitate the conjugative transfer in environmental bacteria. Indeed, copper and zinc were found to accelerate the conjugative transfer of antimicrobial resistance genes in freshwater bacteria ( Wang et al, 2020 ; Wang et al, 2021 ), whereas E. coli strains co-harboring antibiotic and heavy metal resistance (e.g., mer operon and/or silEPS , merBPT , and arsC ) genes have been described in contaminated aquatic environments ( Azam et al, 2018 ; Chen et al, 2019 ; Sultan et al, 2020 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation